PENGARUH AIR LAUT PADA PAVING BLOCK BERBAHAN CAMPURAN FLY ASH DAN ABU SEKAM - M. Shofi’ul Amin; Enes Ariyanto; Faris Fahrur (Jurnal Poli-Teknologi, 2016)
ABSTRACT The utilization of the waste of rice husk ash and fly ash as the materials of making paving blocks was one of the alternative ways in utilizing the waste in Banyuwangi. The previous research conducted by the reduction of 20% cement is still considered quite good for the mixture of paving blocks. Nowadays, many paving blocks are used in feared area of beach which has been thought to be eroded by the sea water. Meanwhile, the sea water contains high salt that can undermine the strenght and the concrete durability. The composition used in making paving blocks is 1:3, 1:4, and 1:5 added by the rice husk ash and the fly ash from 20% of the cement. The number of paving blocks absorption made of the waste of fly ash for the composition 1:3, 1:4 and 1:5 was consecutively shown in 9,73%, 10,91% and 11,30%, while the waste of rice husk ash for the composition 1:3, 1:4 and 1:5 was consecutively shown in 6,97%, 8,14% and 9,15%. The number of axing based on the number of absorption of paving blocks made of the fly ash has the bigger number of axing which was compared to the rice husk ash. Whereas the number of pressure strenght of paving blocks made of the waste of fly ash for the composition 1:3, 1:4 and 1:5 was consecutively shown in 384,63 kg/cm2, 325,43 kg/cm2 and 304,02 kg/cm2. The number of pressure strenght of paving blocks made of rice husk ash for the composition 1:3, 1:4 and 1:5 is consecutively shown in 373,89 kg/cm2, 312,39 kg/cm2 dan 303,63 kg/cm2. Therefore, the making of paving blocks with the waste of fly ash has the bigger strenght compared to the rice husk ash. Keywords: Paving blocks, Fly ash, Rice Husk Ash, Strenght, Sea water ABSTRAK Pemanfaatan limbah abu sekam padi dan fly ash sebagai bahan tambahan pembuatan paving block merupakan salah satu alternatif dalam memanfaatkan limbah didaerah Banyuwangi. Penelitian yang pernah dilakukan dengan pengurangan semen sebanyak 20% masih cukup baik untuk campuran paving block. Saat ini banyak ditemukan paving block yang digunakan untuk daerah-daerah tepi pantai yang dikhawatirkan lama kelamaan akan terkikis air laut. Padahal air laut sendiri memiliki kandungan garam yang tinggi yang dapat menggerogoti kekuatan dan keawetan beton. Komposisi yang digunakan (pasir+semen+abu sekam/fly ash+air). Perbandingan limbah 20% dari berat semen yang digunakan. Nilai resapan paving block berbahan limbah fly ash untuk 1:3, 1:4 dan 1:5 berturut-turut sebesar 9,73%, 10,91% dan 11,30%, dengan bahan limbah abu sekam padi komposisi 1:3, 1:4 dan 1:5 berturut-turut sebesar 6,97%, 8,14% dan 9,15%. Nilai porositas berdasarkan nilai resapan, pada paving block berbahan fly ash memiliki porositas yang lebih tinggi dibandingkan yang berbahan abu sekam padi. Sedangkan nilai kuat tekan paving block berbahan limbah fly ash untuk komposisi 1:3, 1:4 dan 1:5 berturut-turut sebesar 384,63 kg/cm2, 325,43 kg/cm2 dan 304,02 kg/cm2. Nilai kuat tekan paving block berbahan limbah abu sekam untuk komposisi 1:3, 1:4 dan 1:5 berturut-turut sebesar 373,89 kg/cm2, 312,39 kg/cm2 dan 303,63 kg/cm2. Jadi, paving block berbahan fly ash memiliki kekuatan yang lebih tinggi dibandingkan dengan abu sekam padi. Kata Kunci : Paving block, Fly ash, Abu sekam, Kuat tekan, Air Laut